Ensuring the priority of public transport and traffic safety in Tashkent (Международный научный журнал «Инженер», 2026)
This study examines the issues of ensuring road traffic safety in the public transport system of Tashkent city and creating a convenient and safe environment for pedestrians. It also analyzes the directions for the comprehensive development of public transport, the provision of high-quality and safe transport services to passengers, and the improvement of transport infrastructure. The paper highlights modern methods and effective solutions for enhancing traffic safety in public transport.